2020
DOI: 10.5586/am.5512
|View full text |Cite
|
Sign up to set email alerts
|

Problems, Limitations, and Challenges in Species Identification of Ascomycota Members on the Basis of ITS Regions

Abstract: The internal transcribed spacer (ITS) region is regarded as a formal fungal primary barcode with a high probability of the correct identification for a broad group of fungi. ITS sequences have been widely used to determine many fungal species and analysis of rDNA ITS is still one of the most popular tools used in mycology. However, this region is not equally variable in all groups of fungi; therefore, identification may be problematic and result in ambiguous data, especially in some species-rich genera of Asco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…There is a 1% intra-species variation within Aspergillus niger (Henry et al 2000). The ITS sequence of Aspergillus niger (MK461010) is identical to ITS sequences of Alternaria alternata (Baturo-Cieśniewska et al 2020). Further, the ITS sequences of Aspergillus niger (MK461010) shows 10% inter-species variation of ITS sequences of other A. niger strains.…”
Section: Documentation and Personal Errorsmentioning
confidence: 85%
See 3 more Smart Citations
“…There is a 1% intra-species variation within Aspergillus niger (Henry et al 2000). The ITS sequence of Aspergillus niger (MK461010) is identical to ITS sequences of Alternaria alternata (Baturo-Cieśniewska et al 2020). Further, the ITS sequences of Aspergillus niger (MK461010) shows 10% inter-species variation of ITS sequences of other A. niger strains.…”
Section: Documentation and Personal Errorsmentioning
confidence: 85%
“…The ITS region is the formal primary fungal barcode with the highest probability of correct species identification of a broad group of fungi (Horton and Bruns 2001;Bridge et al 2005;Martin and Rygiewicz 2005;Seifert 2009;Bellemain et al 2010;Schoch et al 2012). More than 100,000 ITS sequences of teleomorphic ascomycetes are deposited in international nucleotide sequence databases (Baturo-Cieśniewska et al 2020). Even though, many sequences of correctly identified species are deposited in databases, there are some sequences with technical errors, incorrectly named species, atypical chimeric ITS sequences, and sequences verified only at the generic level or above which makes reliable problems in species identification (Nilsson et al 2009(Nilsson et al , 2014Hongsanan et al 2018).…”
Section: Teleomorphic Ascomycetes Described Based On Only Internal Tr...mentioning
confidence: 99%
See 2 more Smart Citations
“…The nuclear internal transcribed spacer (nrITS) regions of the ribosomal DNA (rDNA) is used as a universal barcoding region, because a broad range of fungi can be identified using this region [ 4 ]. nrITS is still the most widely used for species identification, barcoding and fungal phylogenetics [ 3 , 5 ], although many studies have shown that its utility for species identification was limited [ 6 , 7 , 8 ]. Another commonly used ribosomal marker is the Ribosomal Large Subunit (nrLSU).…”
Section: Introductionmentioning
confidence: 99%